INSTITUTIONAL STRUCTURE FOR CAPITAL ATTRACTION: IMPLICATIONS FOR UKRAINE’S ENTRY INTO THE EUROPEAN UNION - Miller, Dennis D (Journal of European Economy, 2018)
The author discusses the issues of the most attractive and, as Victor Yushchenko puts it, «peaceful» and quiet climate for attracting foreign capital covered in books by Hernando De Soto and William Easterly who studied the eventual entry of Ukraine into the European Union.